Christine de Pizan and the moral defence of women : reading beyond gender - Brown-Grant, Rosalind (Cambridge studies in medieval literature, 1999)
Christine de Pizan's Livre de la Cité des Dames (1405) is justly renowned for its full-scale assault on the misogynist stereotypes that dominated the culture of the Middle Ages. Rosalind Brown-Grant locates the Cité in the context of Christine's defense of women as it developed over a number of years and through a range of different texts. This study shows that Christine's case for women nonetheless had an underlying unity in its insistence on the moral, if not the social, equality of the sexes.